Image of Corruptible Man: Masculinity in the Writings of Athanasius of Alexandria - Rachel Beaver (STFT Jakarta, Indonesia, 2022)
This article offers a reading of Life of Anthony through the lens of gender performance theory and masculinity studies to uncover one fourth-century construction of the ideal Christian man. Through the use of literature contemporary to Athanasius, I argue that Athanasius combined bodily self-presentation with literary and intellectual self-presentation to construct the ideal Christian man and secure his own masculinity in the public eye. One way he achieved this was by creating a hagiographical version of Anthony on whom he could project his own ideological preferences concerning asceticism and masculinity. Athanasius' construction of the Arian as a cunning and feminine figure in his other writings and Anthony as a masculine figure who denounces Arianism effectively typifies fidelity to Nicene orthodoxy as a masculine trait and deviation from Nicene orthodoxy as feminine. This established Anthony as a beacon of masculine orthodoxy for others to emulate.